DNA interaction and anticancer properties of new peripheral phthalocyanines carrying tosylated 4-morpholinoaniline units. (1st February 2020) - Yalazan, Halise; Barut, Burak; Ertem, Beytullah; Yalçın, Can Özgür; Ünver, Yasemin; Özel, Arzu; Ömeroğlu, İpek; Durmuş, Mahmut; Kantekin, Halit
Graphical abstract: Highlights: Morpholine-based new free-base, Co II Pc, Cu II Pc, Zn II Pc, and Mg II Pc were synthesized. New phthalocyanines were verified by common spectroscopic techniques. The photochemical parameters of Zn II Pc (7) were examined. DNA cleavage features of Zn II Pc (7) were investigated. Cyto/phototoxic features of Zn II Pc (7) against cancer cells were examined. Abstract: In this paper, tosylated 4-morpholinoaniline units fused peripherally tetra-substituted free-base (5), copper(II) (6), zinc(II) (7), cobalt(II) (8) and magnesium(II) (9) phthalocyanines (Scheme 1) were reported and these new phthalocyanine conjugates were characterized through Fourier Transform–Infrared (FT– IR) with ATR sampling accessory, Mass Spectra Analysis [Matrix Assisted Laser Desorption/Ionization–Time of Flight–Mass Spectral (MALDI–TOF–MS)] and Ultraviolet–visible (UV–vis) (for all new phthalocyanines), elemental analysis, as well as 1 H and 13 C NMR spectroscopic techniques [for the compounds (2), (4), (5), (7) and (9) ]. The potential utilization of the new peripheral phthalocyanine compounds (7 –9 ) as the new pharmaceutical agents in PDT applications (in oncology and molecular biology) were determined in aspects of pBR322 plasmid DNA cleavage on agarose gel electrophoresis. The results showed that compound (7) cleaved pBR322 plasmid DNA with irradiation. Compound (7) displayed hypochromism without any shift on the addition of increasing concentrations of ct-DNA and Kb of compound (7) was calculated as 2.45 ± (0.20) × 10 4  M −1 . In photochemical studies, the ΦΔ value of compound (7) was determined as 0.11. The cytotoxic/phototoxic properties of compound (7) which had the best photocleavage effects among tested compounds were investigated using MTT assay toward human colorectal (HCT-116) and cervical (HeLa) cancer cells. The cell viabilities of compound (7) were found to be 73 ± 1.6% (HCT-116) and 65 ± 5.5% (HeLa) at 100 µM with irradiation.